2016
DOI: 10.15261/serdj.23.127
|View full text |Cite
|
Sign up to set email alerts
|

Use of Liquefied Dimethyl Ether for the Extraction of Proteins from Vegetable Tissues

Abstract: Dimethyl ether (DME), the simplest ether with the formula CH 3 OCH 3 , is a low-temperature solvent and extraction agent applicable to specialized laboratory procedures as recently demonstrated for extraction of biologically active, flavoring or pungent organic compounds from some biological materials. Due to its low boiling point, DME facilitates the removal of solvent from the samples after extraction. In the present study, we demonstrated the extraction of proteins from juicy or relatively dry vegetable tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…As previously demonstrated [12], liquefied DME can be used as a dewatering solvent actively removing water from plant tissues, therefore, in the present study, we further demonstrated that dewatering and extraction of industrially important components can be achieved in one step under cryogenic conditions.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…As previously demonstrated [12], liquefied DME can be used as a dewatering solvent actively removing water from plant tissues, therefore, in the present study, we further demonstrated that dewatering and extraction of industrially important components can be achieved in one step under cryogenic conditions.…”
Section: Introductionsupporting
confidence: 80%
“…As discussed in our earlier work [12], the low boiling point (-23°C) for DME could be highly beneficial in order to facilitate the removal of the solvent (DME) from the extracted water-containing samples. We have previously demonstrated that, with liquefied DME, extraction of watersoluble proteins from water-containing plant materials such as vegetable tissues can be achieved [12]. The extraction efficiency of water-soluble proteins largely depends on the dewatering action of DME.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, liquefied DME has been used to extract bioactive compounds from citrus leaves and peels (citrus flavonoids) [197], Garcinia mangostana Linn (mangostin) [198], vegetables (proteins) [199], lemon peel tissue (citric acid, vitamin C, and essential oils) [200], tuna liver (fish oil, n-3 polyunsaturated fatty acids) [201,202], macroalgae Monostroma nitidum (Lutein) [203], Japanese knotweed rhizomes (resveratrol and glycoside) [204], Centella asiatica leaves (triterpenoid) [205], hops (α-acids and β-acids) [206], cyanobacteria (fatty acids) [207], sugar mill waste (policosanol and phytosterol) [208], Curcuma longa L. (curcumin) [138], and diatom Chaetoceros simplex var. calcitrans (fucoxanthin) [178] (Figure 5).…”
Section: Extraction Of Functional Components From Natural Resourcesmentioning
confidence: 99%
“…DME has been authorized by the European Food Safety Authority as a safe extraction solvent to produce foodstuffs and food ingredients 20 . Apart from its application as a fuel, subcritical DME has been used for biologically active, flavoring or pungent organic compounds from spices (ginger, black pepper, and chili powder), and its effectiveness is comparable with supercritical carbon dioxide 21 . Most studies on SUPFE have focused on the extraction yield, pressure, temperature, flow rate, and time, but did not focus on the purity of bioactive compounds extracted from SUPFE.…”
Section: Introductionmentioning
confidence: 99%